Analysis of crude oils using gas purge microsyringe extraction coupled to comprehensive two dimensional gas chromatography-time-of-flight mass spectrometry. (15th October 2016) - Gao, Xuanbo; Zhu, Shukui; Zhang, Wanfeng; Li, Donghao; Dai, Wei; He, Sheng
Abstract: As a complex mixture, the analysis of individual compounds in crude oil is a great challenge. The traditional sample preparation method such as column chromatography is time-consuming, solvent-wasting, and very possible to cause the loss of light hydrocarbons. In addition, coelution of compounds with similar boiling points or polarities often occurs in one dimensional gas chromatography–mass spectrometry (1D GC–MS). To overcome these disadvantages, a homemade gas purge microsyringe extraction (GP-MSE) device was prepared and coupled to comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry (GC × GC-TOFMS) for the analysis of crude oils from different regions. The extraction conditions of GP-MSE were optimized in detail. The whole process of GP-MSE extraction only takes 7 min, only 20 μL of organic solvent is needed, and almost complete extraction of analytes is achieved. Compared with the common used methods, light hydrocarbons in all the samples were well retained and more compounds were separated and identified, including diamondoid series, pyrrolic nitrogen compounds and other important biomarkers such as terpane and sterane series. Coelution of compounds in 1D GC–MS was eliminated in GC × GC-TOFMS. Based on the developed GP-MSE-GC × GC-TOFMS, the distribution of trace compounds in crude oils and effect of biodegradation were discussed in detail.